Staphylococcus saprophyticus hemagglutinin binds fibronectin. - Gatermann, S (1994)
Attachment of microorganisms to host tissue is regarded as an important step in the pathogenesis of infections. Staphylococcus saprophyticus adheres to various epithelial cells and hemagglutinates sheep erythrocytes. The hemagglutinin has been identified, but a human target for this surface protein is still not known. In our report, we show that hemagglutinating strains of S. saprophyticus bind to immobilized fibronectin, whereas nonhemagglutinating strains do not. Bacterial binding was inhibited by antibody to the hemagglutinin but not by antibody to Ssp, another surface protein of S. saprophyticus. The purified hemagglutinin but not other surface proteins bound biotin-labeled fibronectin. Binding was saturable and could be inhibited by unbound hemagglutinin, unlabeled fibronectin, and by antibody to the hemagglutinin. We thus conclude that the hemagglutinin of S. saprophyticus may act as a fibronectin receptor in the human host. Heparin, the D3 peptide, or Arg-Gly-Asp-Ser (RGDS) containing peptides did not inhibit binding of fibronectin to the hemagglutinin, indicating that the binding site is different from that of Staphylococcus aureus or Treponema pallidum.